Comparison of two detection systems to reveal AFLP markers in plants - Cara, Nicolás; Marfil, Carlos Federico; Garcia Lampasona, Sandra Claudia; Masuelli, Ricardo Williams (2018)
Since their development, AFLP (amplified fragment length polymorphism) markers have been used for a wide variety of analyses and, up to this day, are considered highly informative, robust, and reproducible molecular markers. Originally, the visualization of the amplified fragments was done in polyacrylamide gels, followed by silver staining or by developing in an X-ray plate, when radioactivity is used. In the last 14 years, capillary electrophoresis of fluorescently labeled fragments has been gradually replacing gel-based systems. However, the latter continue to be better for isolating and cloning AFLP fragments. In this report, we compare the results obtained by capillary electrophoresis with those from silver staining. We found that if fluorescence-labeled amplification products are loaded in a polyacrylamide gel, duplicated bands (doublets) are seen. This phenomenon is probably due to a delay in the migration of the strand that carries the fluorophore. Therefore, we recommend a minimum separation of 4 bp from the nearest fragment to the target fragment for its unambiguous identification and isolation. If this requirement is not fulfilled, an alternative is to make new amplifications using the same primer combination, but with unlabeled primers.